Reoperation for Urinary Incontinence After Retropubic and Transobturator Sling Procedures. Issue 2 (August 2019) - Trabuco, Emanuel C.; Carranza, Daniel; El Nashar, Sherif A.; Weaver, Amy L.; McGree, Michaela E.; Elliott, Daniel S.; Linder, Brian J.; Occhino, John; Gebhart, John B.; Klingele, Christopher J.
Abstract : OBJECTIVE: To compare the reoperation rates for recurrent stress urinary incontinence (SUI) after retropubic and transobturator sling procedures. METHODS: We conducted a retrospective cohort study of all women who underwent midurethral sling procedures at a single institution for primary SUI between 2002 and 2012. To minimize bias, women in the two groups were matched on age, body mass index, isolated compared with combined procedure, and preoperative diagnosis. The primary outcome was defined as reoperation for recurrent SUI. Secondary outcomes included intraoperative complications and mesh-related complications requiring reoperation after the index sling procedure. RESULTS: We identified 1, 881 women who underwent a sling procedure for primary SUI—1, 551 retropubic and 330 transobturator. There was no difference between groups in any of the evaluated baseline variables in the covariate-matched cohort of 570 with retropubic slings and 317 with transobturator slings; results herein are based on the covariate-matched cohort. Women undergoing a transobturator sling procedure had an increased risk of reoperation for recurrent SUI compared with women undergoing a retropubic sling procedure (hazard ratio 2.42, 95% CI 1.37–4.29). The cumulative incidence of reoperation for recurrent SUI by 8 years was 5.2% (95% CI 3.0–7.4%) in the retropubic group and 11.2% (95% CI 6.4–15.8%) in the transobturator group. Women in the retropubic group had a significantly higher rate of intraoperative complications compared with women in the transobturator group (13.7% [78/570] vs 4.7% [15/317]; difference=9.0%, 95% CI for difference 5.3–12.6%); the majority of this difference was due to bladder perforation (7.0% [40/570] vs 0.6% [2/317]; difference=6.4%, 95% CI for difference 4.1–8.7%). The cumulative incidence of sling revision for urinary retention plateaued at 3.2% and 0.4% by 5 years in the two groups. CONCLUSION: Women with primary SUI treated with a retropubic sling procedure have significantly lower cumulative incidence of reoperation for recurrent SUI compared with women who were treated with a transobturator sling procedure. Retropubic slings were associated with a higher risk of sling revision for urinary retention. Abstract : The 8-year cumulative incidence of reoperation for recurrent stress urinary incontinence is two times higher after a transobturator compared with a retropubic sling procedure (11.2% vs 5.2%, respectively).